The vernacular cultural landscape in traditional villages: global hotspots, emerging trends, and a case study of China’s Qilu cultural district - Pan, Zhao; Chen, Yile; Huang, Yuhao; Zheng, Liang (Frontiers in Earth Science, 2024)
China’s rapid economic development has brought challenges to traditional villages, which carry the characteristics of Chinese civilization and traditional culture. Protecting traditional villages is of enormous significance. As a representative of Qilu Cultural District, Shandong has many national-level traditional villages, but some areas lack research on traditional villages and related local cultural landscapes due to various reasons. This study was divided into two parts. First, CiteSpace 6.1.R6 and VOSviewer1.6 software were used to perform a visual bibliometric analysis of the vernacular cultural landscape. Then, China’s Qilu Cultural District (Shandong Province) was taken as a typical case; the literature was read carefully, and an in-depth qualitative analysis was carried out in the research context of the vernacular cultural landscape. This study found that the United States, the United Kingdom, and China have outstanding research results in this field, and the directions of the research have gradually diversified from the early focus on rural and agricultural environments to the later focus on cultural landscape protection, management, and sustainable development. By taking Shandong as an example, the study of traditional villages takes the year 2000 as the starting point and involves architecture, archaeology, culture, and other fields. The architectural field primarily concentrates on the spatial layout, where cultural protection emphasizes the integration of sustainable development using scientific and technological methods, and cultural tourism grapples with the issue of homogenization. Future research needs to improve the literature database, consider local Chinese characteristics, and establish an independent literature database for multidimensional, multifaceted, and cross-cultural research. The direction and focus of this research provide methods and references for subsequent research.